Ridge splitting for horizontal bone augmentation with Guided Bone Regeneration (GBR) and simultaneous implant placement - Agarwal, N; Pai, U Y; Rodrigues, S J; Baral, S (Journal of Nepalese Prosthodontic Society, 2020)
Horizontal lack of residual ridge width can complicate the implant procedures. Therefore, ridge construction prior to implant placement is a biomechanical requirement. Guided bone regeneration, bone grafting, alveolar ridge splitting and combinations of these techniques are used for the lateral augmentation of the alveolar ridge. The ridge splitting technique with simultaneous implant placement seems to be a minimally invasive treatment option for horizontal augmentation of narrow alveolar ridges with adequate vertical height. This paper thoroughly describes a segmental ridge splitting technique with both vertical and horizontal osteotomy cuts followed by the use of chisel and mallet to lateralise the buccal bone which was accompanied by GBR and simultaneous implant placement.